The effect of value climate and trust in the school principal on students well-being - EKŞİ, HALİL (My University, 2022)
In the well-being of the students; teachers, families, schools, environment, cultures, value climate and leader are important factors. It is necessary to know how much these factors affect students’ wellbeing. In this study, the assumption tested is the effect which value climate and the students’ trust in the school principal has on the students’ well-being. Firstly, the Well-Being Model (WBM) is proposed. In this study a quantitative measurement method called correlational pattern model is used. A sample of 256 is included in this model which uses structural equation model and path analysis. The data were collected using the scale of EPOCH (Measure of Adolescent Well-Being), scale of Positive Values (PVS) and the scale of Trust in Principal. For the first stage of the Structural Equation Model (SEM), which is the measurement model, CFA was performed. Then, structural equation is constructed for (WBM) via latent variables and four hypotheses were tested. Compliance indexes showed that WBM was compatible with the data. When the model is examined, the value climate of the school positively and strongly predicts the well-being of the students. The predictive power of the trust in the school principal, however, turned out to be weak. Value climate at school positively affects students’ wellbeing. However, poor trust in the principal has a negative effect on well-being

Öğrencilerin iyi oluşlarında; öğretmen, aile, okul, çevre ve kültürler arası farklılaşma önemli faktörlerdir. Bununla birlikte okullarda değer iklimi ve lider gibi iki önemli faktör vardır. Bu faktörlerin öğrencilerin iyi olma durumları üzerinde ne kadar etkili olduğunun bilinmesine ihtiyaç vardır. Bu çalışmada değer iklimi ve okul müdürüne duyulan güvenin öğrencilerin iyi oluş durumlarına etkili olma durumu araştırılmıştır. Sonuçlara bağlı olarak okullar gerekli tedbirleri almalıdır. Öncelikli olarak İyi Oluş Modeli (İOM) ileri sürülmüştür. Bu çalışmada korelasyonel model adı verilen nicel ölçüm yöntemi kullanılmıştır. Yapısal eşitlik modeli (YEM), yol analizi (PATH) kullanılan bu modelde 256 örneklem yer almıştır. Araştırmada üç ölçme aracı kullanılmıştır. Tüm ölçeklere, YEM in ilk aşaması olan ölçme modeli için DFA yapılmış veri ile orijinal ölçek yapısının uygunluğu test edilmiştir. Daha sonra gizil değişkenler ile İOM için yapısal eşitlik oluşturulmuş ve dört hipotez test edilmiştir. Bu hipotezler doğrultusunda öğrencilerin değer iklimi ve okul müdürüne duyulan güvenin öğrencilerin iyi olma durumlarını yordama gücü test edilmiştir. Kabul edilebilir düzeyde olan uyum indeksleri İOM modelinin verilerle uyumlu olduğunu ortaya koymuştur. Model incelendiğinde okulun değer ikliminin öğrencilerin iyi olma durumlarını pozitif ve kuvvetli bir şekilde yordadığı görülmüştür. Araştırma sonuçlarına göre, okullardaki değer ortamları öğrencilerin iyi oluşlarını doğrudan etkilemektedir. Öğrencilerin bireysel sorumluluklarını yerine getirmeleri okulun değer iklimini olumlu yönde etkiler.
Değer iklimi ve okul müdürüne duyulan güvenin, öğrencilerin iyi oluş durumlarına etkisi
Keywords: Value; trust; well-being; Değer; güven; iyi oluş